Britisch-American Dictionary - Moss, Norman, ....- (Oxford : Helicon Publishing, 1994)
Devided by a common language? Not any more. useful, entertaining, and humorous, The Hutchinson British-American Dictionary enables everyone from both sides of the Atlantic to sidestep the pitfalls that gape for the unwary traveller. It is a vital source for those who are interested in language and its development, and is invaluable for students of British or American English as a second language.